1996
DOI: 10.1016/0167-4889(96)00005-5
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of myeloid differentiation by anti-inflammatory agents, by steroids and by retinoic acid involves a single intracellular target, probably an enzyme of the aldoketoreductase family

Abstract: HL60 cells are human promyeloid cells that can be induced to differentiate by physiological stimuli (e.g. all-trans retinoic acid (ATRA), 1 alpha,25-dihydroxyvitamin D3 (D3), granulocyte colony-stimulating factor (G-CSF)) and by non-physiological agents such as dimethysulphoxide (DMSO) and protein kinase C-activating phorbol esters. The sensitivity of HL60 cells to physiological differentiating agents, but not to DMSO, is enhanced when cells are exposed to 'anti-inflammatory agents' (e.g. indomethacin) or are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 21 publications
1
37
0
Order By: Relevance
“…On the practical side, we asked if combination of low concentrations of 1,25D with COX inhibitors is likely to be useful in the prevention or treatment of human myeloid leukemia, and if so, would selective COX-1 or COX-2 inhibitors be more effective than the non-selective inhibitors previously reported to synergize with 1,25D in HL60 cells. 11,30 We found that leukemia cell lines other than HL60 also exhibit enhanced differentiation, …”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…On the practical side, we asked if combination of low concentrations of 1,25D with COX inhibitors is likely to be useful in the prevention or treatment of human myeloid leukemia, and if so, would selective COX-1 or COX-2 inhibitors be more effective than the non-selective inhibitors previously reported to synergize with 1,25D in HL60 cells. 11,30 We found that leukemia cell lines other than HL60 also exhibit enhanced differentiation, …”
Section: Discussionmentioning
confidence: 90%
“…It was previously reported that in HL60 cells ASA and INDO also have this synergy with 1,25D, but it was not clear if the more specific COX inhibitors are more, or less, effective potentiators of 1,25D-induced differentiation. 11,30 We now show that ASA can be an effective potentiator of 1,25D-induced differentiation not only in HL60 but also in U937, THP-1 cells (Fig. 3) and in primary AML cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Treatment of HL-60 cells with the AKR inhibitors indomethacin or medroxyprogesterone acetate enhances both neutrophil and monocyte differentiation (7,8), and reciprocally, overexpression of AKR1C3 suppresses HL-60 differentiation (8,9). More recently, we have shown that knockdown of AKR1C3 in K562 cells results in erythroid differentiation (10).…”
Section: Introductionmentioning
confidence: 99%
“…BEZ is a lipid-lowering agent that mediates its activity as a ligand of the nuclear receptor PPARa and MPA is an orally active contraceptive progestogen. The study was based on our previous experience in Burkitts lymphoma 9 and acute myeloid leukemia (AML) [10][11][12] (Khanim et al, 2008, unpublished data). We show that both BEZ and MPA induce apoptosis in primary CLL cells and that the combination BEZ þ MPA is significantly more proapoptotic than either agent alone.…”
Section: Introductionmentioning
confidence: 99%